2012
DOI: 10.1016/j.physletb.2012.09.050
|View full text |Cite
|
Sign up to set email alerts
|

Spinning scalar solitons in anti-de Sitter spacetime

Abstract: We present spinning Q-balls and boson stars in four dimensional anti-de Sitter spacetime. These are smooth, horizonless solutions for gravity coupled to a massive complex scalar field with a harmonic dependence on time and the azimuthal angle. Similar to the flat spacetime configurations, the angular momentum is quantized. We find that a class of solutions with a self-interaction potential has a limit corresponding to static solitons with axial symmetry only. An exact solution describing spherically symmetric … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 61 publications
1
31
0
Order By: Relevance
“…This is amply supported by the studies on AdS/CFT correspondence [19,20]. Not only that, Astefanesei and Radu [21], and others [22,23,24,25,26], have shown that such studies also remain meaningful even in the presence of a negative cosmological constant.…”
mentioning
confidence: 73%
“…This is amply supported by the studies on AdS/CFT correspondence [19,20]. Not only that, Astefanesei and Radu [21], and others [22,23,24,25,26], have shown that such studies also remain meaningful even in the presence of a negative cosmological constant.…”
mentioning
confidence: 73%
“…Boson stars and boson shells representing the localized self-gravitating solutions were introduced long ago [1-3] and they have been studied vary widely in the literature . Such theories are being considered in the presence of positive [14][15][16][17] as well as negative [15,[17][18][19][20][21] values of the cosmological constant Λ. The theories with positive values of Λ (corresponding to the de Sitter (dS) space) are relevant from observational point of view as they describe a more realistic description of the compact stars in the universe since all the observations seem to indicate the existence of a positive cosmological constant.…”
Section: Introductionmentioning
confidence: 99%
“…We present a detailed discussion of the various regions in our phase diagram with respect to four bifurcation points. Our theory is seen to have rich physics in a particular domain for positive values of Λ which is consistent with the accelerated expansion of the universe.Introduced long ago [1-3], boson stars represent localized self-gravitating solutions studied vary widely in the literature [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Such theories are being considered in the presence of positive [14-16] as well as negative [17][18][19][20] values of the cosmological constant Λ.…”
mentioning
confidence: 99%